Gall bladder specimen histopathological findings after cholecystectomy - Kumari, Shweta; Kumar, Ajay; Ranjan, Alok; Thakur, Indra Shekhar (International Journal of Research in Medical Sciences, 2023)
Background: Cholecystitis is a generally widespread problem in adult population. Multiple finding has been found in gross and microscopic examination of gallbladder. Existence of stones is one of the known causative factors that lead to histopathological changes in gallbladder. It is also responsible for the development of gallbladder carcinoma. The purpose of this study was to find out the histopathology of gall bladder specimens following surgical intervention. Methods: This observational study included 116 patients admitted in the department of general surgery, PMCH, Patna with acute or chronic cholecystitis from August 2018 to July 2019. Written and informed consent was taken from all the participants. Data was analyzed using SPSS version 20. Results: A total of 116 gallbladder specimens that presented for histopathological examination during the study period were included into the study, with male to female ratio of 1:3. The highest prevalence was found in the age group of 31-50 years. The results of histopathological examination of these gallbladder specimens showed that chronic cholecystitis was found in 93 (80.1%), acute cholecystitis in 17 (14.6%), and dysplasia was found in 5 (4.3%) patients, and gall bladder carcinoma was detected in 1 (0.8%) patients. On morphological analysis, the commonest gall stones were made up of cholesterol and the most common lesion was chronic cholecystitis by histopathology. Conclusions: This study concludes that the chronic calculus cholecystitis was dominant in our population. It is assumed that routine histopathological examination following cholecystectomies essential for all gallbladder specimens even in the non-existence of macroscopic signs of carcinoma, which was the case in our patients.